PRODUCTION PROCESS IN ECONOMIC RELATION SYSTEM - A. I. Vankevich (Наука и техника)
Production is considered as a process, where people, being interconnected by some certain production relations, create material benefits in the form of means of production and personal items that are necessary for people existence. The production involves two components - productive forces and production relations of people. Production is to be carried out continuously because in the place of the used benefits it is necessary to create new ones with taking into account materia! and spiritual needs of the society. It follows from the above-mentioned facts that it plays the main role in the system of economic relations..